PROPAGATING RIFT DURING THE OPENING OF A SMALL OCEANIC BASIN: THE PROTECTOR BASIN (SCOTIA ARC, ANTARCTICA) - Galindo-Zaldívar J.; Bohoyo F.; Maldonado A.; Schreider A.; Suriñach E.; Vázquez J.T. (My University, 2006)
The opening of oceanic basins constitutes one of the key features of Plate Tectonics because it determines the rifting and displacement of the continental crustal blocks. Although the mechanisms of development of large oceans are well known, the opening and evolution of small and middle size oceanic basins have not been studied in detail. The Protector Basin, located in the southern Scotia Sea, is a good example of a small oceanic basin developed between two thinned continental blocks, the Pirie Bank and the Terror Rise, poorly studied up to now. A new set of multibeam bathymetry, multichannel seismic reflection, and gravity and magnetic anomaly profiles obtained on the SCAN 2001 cruise led us to determine that the Protector Basin probably opened during the period comprised between C5Dn (17.4 Ma) and C5ACn - 5ABr chrons (13.8 Ma), forming a N - S oriented spreading axis. The end of spreading is slightly younger to the north. The start of spreading is clearly diachronous, with the most complete set of chrons up to C5Dn in the southern profile, C5Cn in the middle section and only up to C5ADn in the northern part of the basin. The spreading axis propagated northwards during the basin development, producing the wedge shape of the basin. In addition, at the NE part of the basin, a reverse fault developed in the border of the Pirie Bank after basin opening accentuates the sharp northern end. Moreover, the northwestern part of the Pirie Bank margin is an extremely stretched continental crust with N - S elongated magnetic anomalies related to incipient oceanic southward propagating spreading axes. The Protector Basin shows the oldest evidence of E - W continental stretching and subsequent oceanic spreading during Middle Miocene, related with the eastward development of the Scotia Arc that continues up to Present. The relative rotation of continental blocks during the development of small sized oceanic basins by continental block drifting favoured the opening of wedge shape basins like the Protector Basin and conjugate propagating rifts. © 2005 Elsevier B.V. All rights reserved.
Keywords: MIDDLE MIOCENE; OCEANIC SPREADING; PROPAGATING RIFT; SCOTIA ARC; SEAFLOOR MAGNETIC ANOMALIES; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene